ANALISIS PROGRAM PELATIHAN DAN PENGEMBANGAN PEGAWAI : PENGARUHNYA TERHADAP PENINGKATAN KEMAMPUAN PEGAWAI (Studi Pada UPTD Pengembangan Produktivitas Daearah, Dinas Tenaga Kerja dan Transmigrasi Provinsi Kalimantan Timur) - Eryanto, Rudy Heri (PREDIKSI, 2012)
This study aimed to determine whether the Employee Training and Development to have a positive impact pegaruh Upgrades employee.The results showed that there is a positive and significant relationship between the variables Employee Training and Development Capacity Employees variables. It can be seen from the results of a statistical test in which the correlation coefficient (r) is equal to 0.865, which means there is a strong relationship between the two variables. The result was greater when compared to the table of critical prices Product Moment Correlation coefficients (Pearson) for n = 21 at the 5% significance level, ie 0.433. Or it can be said also that rhit = 0.865> rtab = 0.433, which means that there is a strong relationship between the two variables..